Cryotherapy for cervical lesions: efficacy and patient satisfaction - Katakdhond, Shriraj; Samant, Padmaja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vaginal discharge is a distressing commonplace gynecological condition seen in all age groups albeit from different causes. This study evaluates the outcome of cryotherapy on benign cervical lesions over a period of 2 years in a tertiary care centre. Efficacy of cryotherapy in making patient symptom free. Efficacy of cryocauterization in healing the cervical lesion. Methods: This is prospective observational study of 30 women of reproductive age group attending outpatient department for complaint of vaginal discharge. Cervical cytology was performed for all women and out of the women advised cryotherapy, those fitting inclusion criteria and consenting for study were enrolled. Their findings and investigations were noted. After they underwent cauterization, they were followed for period of 3 months. Findings, complications and level of satisfaction were noted down. Results: Healing of cervical lesion was complete in 96% women at the end of 12 weeks. There was 1 failure of therapy among sample size of 30. Satisfaction rate was high. Conclusions: Cervical cryocauterization is a cheap, effective and simple procedure for treatment of cervical lesions. There are few complications and patient satisfaction is high. It is an easily accessible and safe procedure and helps preserve fertility of women at the same time addressing the vaginal discharge.